Decoding competitive endogenous RNA regulatory network in postoperative cognitive dysfunction - Wang, Wei; Huo, Pengwei; Zhang, Lei; Lv, Gang; Xia, Zhongyuan (Frontiers in Neuroscience, 2022)
Postoperative cognitive dysfunction (POCD) is a common postoperative neurological complication in elderly patients. Circular RNAs (circRNAs) are abundant in the mammalian brain and can probably regulate cognitive function. However, the competitive endogenous RNA (ceRNA) regulatory network in POCD remains illiterate. Transcriptomic signatures in the hippocampus of POCD mice derived from the Gene Expression Omnibus (GEO) dataset GSE190880, GSE95070, and GSE115440 were used to identify the circRNA, miRNA, and mRNA expression profiles of POCD mice compared with controls, respectively. A set of differentially expressed RNAs, including 119 circRNAs, 33 miRNAs, and 49 mRNAs were identified. Transcript validation showed the enhanced expression of circ_0001634, circ_0001345, and circ_0001493. A ceRNA regulatory network composed of three circRNAs, three miRNAs, and six mRNAs was established. The hub mRNAs in the ceRNA network were further found to be involved in the hormone catabolic process and regulation of canonical Wnt signaling pathway, revealing their crucial role in POCD. Finally, three miRNAs and four mRNAs were verified by qRT-PCR. These results based on bioinformatics and PCR array suggest that circ_0001634/miR-490-5p/Rbm47, circ_0001634/miR-490-5p/Sostdc1, circ_0001634/miR-7001-5p/Sostdc1, circ_0001345/miR-7001-5p/Sostdc1, and circ_0001493/miR-7001-5p/Sostdc1 may be novel diagnostic biomarkers and therapeutic targets for POCD.